2018
DOI: 10.1002/adem.201800017
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviors of Long‐Period Stacking Ordered Structure in Mg Alloys Used in Biomaterials: A Review

Abstract: The long‐period stacking ordered (LPSO) phases have distinctive microstructures and significant effect on the promotion of mechanical properties of Mg alloys, which have received considerable attention not only as industrial materials but also as biodegradable implant materials recently. By now, numerous researchers devote to study the effects of the microstructures of LPSO phases on the mechanical properties of Mg alloys. But a few of them reveal the relationship between LPSO phases and corrosion behaviors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 136 publications
0
13
0
Order By: Relevance
“…As the lightest structural metal on earth, magnesium has obvious advantages of rich resource, ease of recycling, and good biocompatibility [1][2][3]. These unique properties make magnesium and its alloys attractive for automotive, aerospace, and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…As the lightest structural metal on earth, magnesium has obvious advantages of rich resource, ease of recycling, and good biocompatibility [1][2][3]. These unique properties make magnesium and its alloys attractive for automotive, aerospace, and biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The EDS (Figure 1f–h) and XRD patterns ( Figure ) revealed that the block shape phase was 18R–LPSO phase (Mg 12 YZn) and the eutectic structure was W phase (Mg 3 Zn 3 Y 2 ), which was agreed with the phase diagram [ 29 ] and previous reports. [ 27,28 ] X‐ray phase analysis showed that when Al was added to the based alloy, a new diffraction peak emerged, which was named as Al(Y, Zn) in this article according to EDS results (Figure 1h and Figure 5). The EDS results showed that the new phase was rich in Al, Zn, and Y element.…”
Section: Resultsmentioning
confidence: 66%
“…[ 28 ] Hydrogen evolution experiment was to collect hydrogen (H 2 ) produced during the reaction into the burette above the samples. The average corrosion rates from mass loss ( P w mm/y) and hydrogen evolution ( P AH mm/y) were calculated by following equations [ 28 ] PnormalW=2.10(WW0)/A1t1PAH=2.006Vnormalh/A2t2where W (mg) was the weight before immersion and W 0 (mg) was the weight after removing corrosion products. t 1 and t 2 were the immersion time ( t 1 = t 2 , days) and the area exposed to the solution ( A 1 = A 2 , cm 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…In general, by adjusting the Zn/Y atomic ratio, three kinds of ternary equilibrium phases can be obtained in the Mg–Zn–Y alloys, namely, LPSO phase, I phase, and W phase . Among them, LPSO phase is an excellent strengthening phase which is tightly combined with the α‐Mg matrix and could effectively improve the mechanical and corrosion properties . There are various methods for improving the performance of Mg–Zn–Y alloys containing LPSO, such as the production of new alloys by introducing alloying elements (Zr, Sr, B, Ti, and Mn) or ceramic particles (B 4 C and TiB 2 ), various novel casting methods by ultrasonic and electromagnetic stirring treatment, and grain refinement by severe plastic deformation (hot extrusion, rolling, and equal channel angular pressing) .…”
Section: Introductionmentioning
confidence: 99%